Biocatalytic Conversion of Avermectin to 4"-Oxo-Avermectin: Heterologous Expression of the ema1 Cytochrome P450 Monooxygenase - Molnár, István (American Society for Microbiology, 2005)
The cytochrome P450 monooxygenase Ema1 from Streptomyces tubercidicus R-922 and its homologs from closely related Streptomyces strains are able to catalyze the regioselective oxidation of avermectin into 4"-oxo-avermectin, a key intermediate in the manufacture of the agriculturally important insecticide emamectin benzoate (V. Jungmann, I. Molnár, P. E. Hammer, D. S. Hill, R. Zirkle, T. G. Buckel, D. Buckel, J. M. Ligon, and J. P. Pachlatko, Appl. Environ. Microbiol. 71:6968-6976, 2005). The gene for Ema1 has been expressed in Streptomyces lividans, Streptomyces avermitilis, and solvent-tolerant Pseudomonas putida strains using different promoters and vectors to provide biocatalytically competent cells. Replacing the extremely rare TTA codon with the more frequent CTG codon to encode Leu4 in Ema1 increased the biocatalytic activities of S. lividans strains producing this enzyme. Ferredoxins and ferredoxin reductases were also cloned from Streptomyces coelicolor and biocatalytic Streptomyces strains and tested in ema1 coexpression systems to optimize the electron transport towards Ema1.